2020
DOI: 10.1177/1715163520915230
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacists’ perceptions of their working conditions and the factors influencing this: Results from 5 Canadian provinces

Abstract: Introduction: Our previous study in British Columbia (BC) indicated that pharmacists have a poor perception of their working conditions. The objective of this study is to assess pharmacists’ perceptions of their working conditions in 4 other Canadian provinces. Methods: This was a cross-sectional study across Alberta, New Brunswick, Prince Edward Island and Newfoundland and Labrador, using a survey adapted from the Oregon Board of Pharmacy. Data collected previously from BC were also included in the analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…In an unprecedented “infodemic”, inaccurate and incomplete information about coronavirus spread rapidly adding to the fear and the anxiety of the public [ 39 , 42 , 43 ]. Most of respondents reported not having enough time to devote to clients, but such lack of time was observed even in non-pandemic circumstances [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an unprecedented “infodemic”, inaccurate and incomplete information about coronavirus spread rapidly adding to the fear and the anxiety of the public [ 39 , 42 , 43 ]. Most of respondents reported not having enough time to devote to clients, but such lack of time was observed even in non-pandemic circumstances [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“… 16 A follow-up study expanding the evaluation to additional provinces in Canada demonstrated a poor perception of working conditions among pharmacist respondents, which may contribute to occupational burnout. 17 …”
Section: Discussionmentioning
confidence: 99%
“…16 A follow-up study expanding the evaluation to additional provinces in Canada demonstrated a poor perception of working conditions among pharmacist respondents, which may contribute to occupational burnout. 17 Based on the 2019 United States (U.S.) National Pharmacist Workforce Study, 6% of pharmacists in the U.S. were working in an ambulatory care setting between 2014 and 2019. 18 Pharmacist burnout was assessed using the Professional Fulfillment Index, that correlates with the MBI.…”
Section: Discussionmentioning
confidence: 99%
“…However, in many jurisdictions, these changes have been slow to be implemented producing additional work-related stress [ 3 , 4 ]. Studies around the globe have continued to identify common factors contributing to workplace stress for pharmacists in the past decade [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from the Oregon Board of Pharmacy survey on pharmacists’ perception of their working conditions [ 21 ], Tsao et al initially surveyed pharmacists working in British Columbia, Canada in 2013 [ 22 ] and then extended the survey to include four other Canadian provinces (Alberta, New Brunswick, Newfoundland, and Prince Edward Island) to further identify aspects that contributed to Canadian pharmacists’ perspectives of their working conditions [ 23 ]. The results show that the majority were satisfied that their working environment assisted in delivering safe and effective patient care; however, most were dissatisfied by the inadequate break time for lunch, staffing levels, and duration to complete their task at hand.…”
Section: Introductionmentioning
confidence: 99%